Parque nacional do iguaçu e a nova ferroeste: potenciais consequências do megaprojeto de infraestrutura ferroviária - Oliveira, Thaís de (2023)
The present work proposes to contextualize the implementation of Nova Ferroeste, potential consequences and effects, considering its proximity to the Iguaçu National Park. As a methodological proposal, it is based on document analysis, developing into three main presentations, which will present the challenges of the Iguaçu National Park region, its management instruments, strategic plans and adversities as well as the situation of the cities that influence and are influenced directly by the UC; in a second moment, the investment plans that are being implemented for this territory and Nova Ferroeste itself; and, finally, to analyze this context of this projected urban environment and landscape planning, the SWOT methodology is proposed for the analysis of prospective scenarios. Through the study by the proposed approach, the uniqueness of this region is demonstrated, as well as its (mega)challenges to overcome in this recognition of the current territorial scenario and the planned plans for the territory. There is regional unpreparedness for the predicted scenario, many overlapping projects for the same region without considering the synergistic cumulative impacts, showing gaps in the environmental assessment documents for the region. It is concluded that the positive scenario is possible as long as standards based on sustainability and territorial reality are reviewed, discarding outdated models